Caribbean cultural landscapes and otherness in the journal "Viage a la America" to Fray Íñigo Abbab y Lasierra (1772-1774) - Rodríguez Velásquez, Fidel (2018)
The present work studied the construction of cultural landscapes and Caribbean alterities in the diary of “Travel to America” by fray Íñigo Abbad y Lasierra (1772-1774). To this end, a textual analysis was made of his daily chronicle of events in the crossing of the islands of Puerto Rico, Margarita and Trinidad, in order to account for the way he lived the geographies, people, animals and customs of these regions. The story of this Benedictine Friar can be understood from two dimensions, an anthropological one that accounts for the cultural universe of the traveler in which elements of European enlightenment were found with elements of medieval Europe, and a sociohistorical dimension that accounts for the efforts of this traveler to see the region as a backward space but with an important potential that has been little used by those who inhabit these regions and by those who were sent by the Spanish crown to do so. From these two dimensions emerge the cultural landscapes that fray Íñigo Abbad y Lasierra textually represent in his travel diary.